CLASSIFICATION OF MANGROVE ECOSYSTEM AREA IN PANTAI BAHAGIA VILLAGE, MUARA GEMBONG, BEKASI REGENCY, USING SENTINEL IMAGERY WITH NORMALIZED DIFFERENCE VEGETATION INDEX METHOD (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
Mangrove ecosystems are one type of coastal resources that has benefits in physical, biological, and economic wise. Mangrove ecosystems in Muara Gembong are ecosystems that are included in the category of protected forest. This research aims to estimate the area of mangrove forests and classify its canopy cover. The method used in this study is the Normalized Difference Vegetation Index (NDVI) and using sentinel imagery (with a spatial resolution of 10 m). The canopy cover classification applied in this study refers to the Indonesian Ministry of Forestry standards. Canopy cover data was validated with a densiometer to estimate the percentage of mangrove canopy cover. The results showed that the area of mangrove forests reached 301.83 ha with a high-density level or a tight cover class reaching 59.31% or 179.02 ha. The area of mangroves in Pantai Bahagia Village, Bekasi Regency, has increased from the last few years due to rehabilitation actions taken by several local communities.